The divide - Clark, Aubrey (London: Hodder Children's, 2012)
Cassie's evil half-sister has surfaced and won't rest until she has taken Cassie's place in the circle, also a band of powerful witch-hunters are targeting the group, determined to destroy them. Will the circle remain intact despite the powerful evil magic that has infiltrated their ring?
Keywords: Young adult fiction